Sustainable banana (Musa spp) production through integrated plant nutrition system - A review - HAZARIKA, T K; NAUTIYAL, B P; BHATTACHARYYA, R K (The Indian Journal of Agricultural Sciences, 2015)
Nutrient depletion is a reversible constraint and therefore high agricultural production can be realized with appropriate soil nutrient management. Careful manipulation of nutrient stocks and flows, in order to achieve satisfactory and sustainable level of agricultural production is the Integrated Plant Nutrient System (IPNS). IPNS is holistic and sustainable approach to attain the maximum profitability and cost benefit ratio for the farmers. It is nutrient saving, controls erosion and recycles crop residues, manures and other biomass or nutrient adding. Different IPNS packages have been reported to improve growth and yield of banana (Musa spp). Through combined application of chemical fertilizers, organic manures, bio-fertilizers and bio-control agents in IPNS have profound effect in improving quality parameters like total soluble solids (TSS), ascorbic acid, total reducing and non-reducing sugars of banana. It also improves the physical, chemical and biological properties of soil, especially the number of beneficial soil microflora. Considering the ill effects of chemical fertilizers, it is high time to use IPNS in banana cultivation instead of using chemical fertilizers alone. The paper reviews all the literature on various aspects of banana cultivation from the IPNS perspective for better understanding and future strategies for improved production as well as quality of banana.